2015
DOI: 10.1007/s00063-015-0095-y
|View full text |Cite
|
Sign up to set email alerts
|

Qualitätssicherungskonzepte in der Intensivmedizin

Abstract: Intensive care medicine (ICM) is characterized by a high degree of complexity and requires intense communication and collaboration on interdisciplinary and multiprofessional levels. In order to achieve good quality of care in this environment and to prevent errors, a proactive quality and error management as well as a structured quality assurance system are essential. Since the early 1990s, German intensive care societies have developed concepts for quality management and assurance in ICM. In 2006, intensive c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0
8

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 29 publications
0
1
0
8
Order By: Relevance
“…Moreover, it has previously been shown that both benchmarking and internal quality control improve patient safety and management [ 24 , 31 ]. Although systems of quality comparison are available in Europe (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it has previously been shown that both benchmarking and internal quality control improve patient safety and management [ 24 , 31 ]. Although systems of quality comparison are available in Europe (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Zuvor wurde in der administrativen und organisatorischen Welt des deutschen Krankenhauses die Intensivstation mitunter als belastender Kostenfaktor oder auch gerne als wichtige Einnahmequelle wahrgenommen [1]. Die Intensivstation ist jedoch zunächst einmal der Ort, an dem schwerstkranke Patient*innen zeitnah intensiv behandelt, überwacht und multiprofessionell auf hohem Niveau versorgt werden müssen [2].…”
Section: Qualitätssicherung Mit Herz Und Verstandunclassified
“…Gemäß der Leitidee des Vaters der Managementlehre Peter F. Drucker "Management is doing things right; leadership is doing the right things", bedarf es v. a. in der Intensivmedizin sowohl eines proaktiven Qualitäts-und Fehlermanagements als auch einer strukturierten Qualitätssicherung (QS) [3]. Qualitätsmanagement (QM) in der Intensivmedizin ist eine Aufgabe des gesamten interdisziplinären und interprofessionellen Teams [1,3,5,6].…”
Section: Merkeunclassified
See 1 more Smart Citation
“…Dabei beansprucht sie überproportional viele Ressourcen der stationären Versorgung und des Budgets. In deutschen Krankenhäusern gilt die Intensivstation daher mitunter als belastender Kostenfaktoraber mittlerweile auch als wichtige Erlösquelle [1]. Zwischen 2002 und 2016 hat sich die Gesamtzahl der Krankenhäuser in Deutschland um 12,1 % verringert, die der mit Intensivmedizin sogar um 14,6 % [4].…”
unclassified